OPPORTUNITIES FOR UZBEKISTAN TO USE THE EXPERIENCE OF DEVELOPED COUNTRIES IN IMPROVING THE EFFICIENCY OF COMMERCIAL BANKS’ ASSETS (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the issues of increasing the efficiency of commercial banks' assets, their assessment criteria, and the possibilities of using the experience of the banking system of developed countries. During the study, special attention was paid to the profitability of bank assets, asset quality, liquidity indicators, and the effectiveness of the risk management system. Also, the experiences of diversifying the asset portfolio, developing risk management systems, and introducing digital technologies used in banks in the United States and European countries were studied. A comparative analysis was carried out with the activities of commercial banks of Uzbekistan, identifying existing problems and ways to eliminate them. Based on the results of the study, scientific and practical proposals were developed to increase the efficiency of bank assets, reduce credit risks, and ensure the stability of the banking system.